Persistent lipid abnormalities in statin-treated patients and predictors of LDL-cholesterol goal achievement in clinical practice in Europe and Canada - Gitt, Anselm Kai (European journal of preventive cardiology, 2012)
Background: The prevalence of persistent lipid abnormalities in patients receiving statins in primary and secondary care is needed to formulate recommendations for future treatment. Studies associating cardiovascular risk factors with lipid target goal achievement are lacking., Design: A cross-sectional, observational study that assessed the prevalence of persistent dyslipidemia in patients treated with statins and analyzed predictors of lipid target achievement., Methods: Serum lipid values of 22,063 statin-treated patients were studied in the context of their cardiovascular risk factors, and the potency and composition of their lipid-lowering treatment. European Society of Cardiology recommendations were used to classify patient risk, and to define LDL-cholesterol goal and normal levels for HDL-cholesterol and triglycerides., Results: Overall, 48.2% of patients did not achieve the therapeutic goal for LDL-cholesterol, either as a single lipid anomaly or associated with low HDL-cholesterol, elevated triglycerides, or both. Lack of goal achievement was more prevalent among low-risk patients (55.8%) than high-risk patients (46.8%). Serum LDL-cholesterol levels were lower in high-risk patients. Predictors associated with LDL-cholesterol goal achievement were higher statin dose (odds ratio (OR): 0.35), specialist treatment (OR: 0.74), or combined lipid-lowering therapy (OR: 0.80)., Conclusions: Nearly half of statin-treated patients missed their therapeutic LDL-cholesterol goal, highlighting a gap between recommendations and clinical practice. Better achievement of LDL-cholesterol therapeutic goal was found among patients at high cardiovascular risk, those on high statin doses or using combination therapy, and patients managed by specialists. Results suggest that residual dyslipidemia in statin-treated patients at low cardiovascular risk may be reduced by increasing statin dose.
First published March 10, 2011
Gesehen am 02.07.2018